2010
DOI: 10.1097/qad.0b013e32833a097b
|View full text |Cite
|
Sign up to set email alerts
|

Viremia and drug resistance among HIV-1 patients on antiretroviral treatment: a cross-sectional study in Soweto, South Africa

Abstract: Background: We assessed risk factors for viremia and drug resistance (DR) among long-term recipients of antiretroviral therapy (ART) in South Africa.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

22
105
4

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 110 publications
(131 citation statements)
references
References 37 publications
22
105
4
Order By: Relevance
“…In the present study, we examined patients from the public health system and found a high rate of drug resistance mutations: 76.39% of the samples tested (55/72) had at least one drug resistance mutation after a median follow-up period of 40 months. This rate of drug resistance mutation is similar to that recently reported in studies in decentralized areas of Senegal (18) and in other countries such as the Central African Republic (19) and the Republic of South Africa using the same first-line regimens (20). In contrast, a relatively low prevalence of resistant viruses has been reported in Cameroon after 12 and 24 months, probably because of the shorter median follow-up period of 17 months (21).…”
Section: Discussionsupporting
confidence: 89%
“…In the present study, we examined patients from the public health system and found a high rate of drug resistance mutations: 76.39% of the samples tested (55/72) had at least one drug resistance mutation after a median follow-up period of 40 months. This rate of drug resistance mutation is similar to that recently reported in studies in decentralized areas of Senegal (18) and in other countries such as the Central African Republic (19) and the Republic of South Africa using the same first-line regimens (20). In contrast, a relatively low prevalence of resistant viruses has been reported in Cameroon after 12 and 24 months, probably because of the shorter median follow-up period of 17 months (21).…”
Section: Discussionsupporting
confidence: 89%
“…Patient samples (n ϭ 38) from the South African Virological Evaluation (SAVE) study (9) and a workplace HIV program within the mining industry (26) and samples submitted for routine genotyping were selected for resistance phenotyping (27). Samples were selected on the basis of availability and the presence of one or more NNRTI resistance-associated mutations.…”
Section: Hiv-1 Subtype C Sequencesmentioning
confidence: 99%
“…Sequences were obtained from the South African Treatment and Resistance Network (SATuRN) database (http://www.bioafrica.net/regadb/) (n ϭ 766) (9) and the Stanford HIV Drug Resistance Database (HIVdb) (http://hivdb .stanford.edu/) (n ϭ 667). Only sequences with NNRTI resistance-associated mutations were included.…”
Section: Hiv-1 Subtype C Sequencesmentioning
confidence: 99%
See 1 more Smart Citation
“…In one study conducted in Soweto, SA, about one-third of patients receiving the second-line lopinavir/ritonavir (LPV/r)-based regimen were found to be viraemic. [7] In another study in Khayelitsha, SA, patients receiving second-line ART were less likely to be virologically suppressed than patients remaining on first-line ART at equivalent durations of treatment (odds ratio (OR) 0.51; 95% confidence interval (CI) 0.26 -1.01). [8] North American and European ART guidelines recommend that genotyping governs decisions on the appropriate treatment for patients failing second-line ART.…”
mentioning
confidence: 99%